Proposed Service Recovery Strategies for Jenius BTPN (The Indonesian Journal of Business Administration, 2021)
The digital era creates new opportunities and new competitors in the financial and banking industry, marked by the emergence of Financial Technology (Fintech), digital payments, cryptocurrency, and also digital banking. The use of digital banking has become a way of banking transactions that is increasingly prevalent today. People are starting to shift from conventional transactions to using digital banking services. Jenius is a digital banking application launched by Bank BTPN. They launched a digital-based financial application specifically designed to help people manage finances through smart phones. In its implementation, Jenius experienced problems, namely due to service failures that caused customers to experience problems and make complaints about their performance. Therefore, the aim of this study is to find out what are the causes of customer complaints and to find out which service recovery strategy is most appropriate for customers after a service failure. This study uses a combined method of qualitative and quantitative research to assess Jenius's external and internal environment. First, general environmental analysis, competitor analysis and customer analysis are carried out to assess Jenius' external environment. Second, this research analyzes the company's internal situation using the marketing mix analysis approach and current service recovery analysis conducted by Jenius. The overall results of the analysis are then summarized in a SWOT analysis; as well as being an input to identify the root causes of these business problems. As a result, this research will found the root of the problem that occurred in terms of internal and external factors from Jenius, which caused the gap between the service recovery strategies that had been implemented still not in accordance with the expectations of customers. Then, formulating solution based on the TOWS matrix approach. Three alternative solutions which are then divided into seven strategies relevant to the root of the problem are used to develop a service recovery strategy. The next implementation plan is developed in such a way that the proposed strategy can increase customer satisfaction and customer intention to be loyal to Jenius. Keywords: Service Failure, Service Recovery Strategy, Digital Banking, Jenius